Association of Phthalate Exposure with Thyroid Function and Thyroid Homeostasis Parameters in Type 2 Diabetes. (27th October 2021) - Chen, Yi; Zhang, Wen; Chen, JingSi; Wang, Ningjian; Chen, Chi; Wang, Yuying; Wan, Heng; Chen, Bo; Lu, Yingli
Abstract : Aims . Phthalates, which are recognized environmental endocrine-disrupting chemicals, are associated with thyroid hormone disruption. We aimed to evaluate the relationship of phthalate metabolites with thyroid function and thyroid homeostasis parameters in type 2 diabetes and to explore whether thyroid autoimmunity status and metformin, the most common antidiabetic drug, may influence such associations. Methods . Concurrent urine and blood samples were collected from 639 participants with type 2 diabetes in the METAL (Environmental Pollutant Exposure and Metabolic Diseases in Shanghai) study. We measured urinary concentrations of thirteen phthalate metabolites along with serum levels of thyroid-stimulating hormone (TSH), total T4 and T3, free T4 (FT4 ) and T3 (FT3 ), thyroid peroxidase antibody (TPOAb), and thyroglobulin antibody (TgAb). Four parameters of thyroid homeostasis, including the sum activity of step-up deiodinases (SPINA-GD), thyroid secretory capacity (SPINA-GT), Jostel's TSH index (TSHI), and thyrotroph thyroid hormone resistance index (TTSI), were also calculated. Results . Among all participants, after full adjustment, multivariable regression analysis showed that some urine phthalate metabolites were negatively associated with TSH, TSHI, and TTSI levels and positively associated with FT3, T3, SPINA-GD, and SPINA-GT levels. None of the urine phthalate metabolites exhibited a significant association with thyroid autoimmunity. The associations of phthalate metabolites with thyroid function and thyroid homeostasis parameters differed based on thyroid autoantibody and metformin treatment status. Conclusions . Urinary phthalate metabolites may be associated with thyroid function and thyroid homeostasis parameters among participants with type 2 diabetes. Furthermore, our present study suggested that thyroid autoantibody status and metformin treatment status are potential mediators of such associations.